Analisis Isi Buku “Ayo Belajar Bahasa Arab” Untuk Kelas Satu Madrasah Ibtida’iyah - Mirza Mahfud; Ahmad Reza (Program Studi Pendidikan Bahasa Arab Sekolah Tinggi Bahasa Arab dan Dakwah Masjid Agung Sunan Ampel Surabaya, 2024)
Textbooks play an important role in the teaching and learning process, including in learning Arabic. For children in the first grade of Madrasah Ibtida'iyah, Arabic textbooks are the main medium for introducing and developing their Arabic language skills. Therefore, it is important to analyze the contents of Arabic textbooks to ensure their suitability to the learning objectives and needs of children in the first grade of Madrasah Ibtida'iyah. This research aims to analyze the suitability of the content of the book Let's Learn Arabic for first grade Madrasah Ibtida'iyah regarding its suitability to the content of the material for the Core Competencies and Basic Competencies. The type of research used is library research. Meanwhile, in analyzing the data the author used descriptive analysis and content analysis. The data collection method is obtained from analysis, observation and documentation. The subject and object at the same time are books Come on, learn Arabic for first grade Madrasah Ibtida'iyah. The results of the research show that the contents of the book are appropriate Come on, learn Arabic for first grade Madrasah Ibtida'iyah with Core Competencies and Basic Competencies, the existing teaching materials are suitable in terms of content, arrangement and graphics to be used and taught to first grade students at Madrasah Ibtida'iyah if they already know all the letters and are in accordance with the Core Competencies and Basic Competencies, but for learning purposes In each sub-section there is nothing special and only the general purpose. Therefore, perhaps we can recommend this book for children who are still in elementary school. Because each chapter consists of sub-discussions accompanied by various exercises. The material between chapters is interconnected and the form of material and exercises are tiered from Chapter I – Chapter VI.